N′-[(2-n-Butyl-4-chloro-1H-imidazol-5-yl)methylidene]adamantane-1-carbohydrazide sesquihydrate ethanol hemisolvate - Abdul-Malek, S.Al-Tamimi; Ahmed, B.; Mohamed, A. Al-Omar; Ali A, El-Emam; Ng, Seik Weng (International Union of Crystallography, 2010)
In the asymmetric unit of the title compound, C19H27ClN4O·0.5C2H6O·1.5H2O, there are two molecules of the Schiff base, which has a rigid adamantyl cage at one end of the C(= O)NH–N=CH– chain and an almost planar [torsion angles = 1.3 (1) and 7.9 (2)° imidazolyl ring at the other end, three molecules of water and one molecule of ethanol. In both independent molecules of the Schiff base, this chain displays an extended zigzag configuration. All their amino groups function as hydrogen-bond donors to water molecules; these are linked to other acceptor atoms, generating a layer structure. O—H[cdots, three dots, centered]O and O—H[cdots, three dots, centered]N interactions involving the water molecules also occur.